2022
DOI: 10.18632/aging.204444
|View full text |Cite
|
Sign up to set email alerts
|

Starvation-induced long non-coding RNAs are significant for prognosis evaluation of bladder cancer

Abstract: Background: Starving intratumoral microenvironment prominently alters genic profiles including long noncoding RNAs (lncRNAs), which further regulate bladder cancer (BCa) malignant biological properties, such as invasion and migration. Methods: Transcriptome RNA-sequencing data of 414 BCa tumor tissues and 19 normal tissues were obtained from TCGA database and paired samples of 132 BCa patients. A chain of in vitro validations such as qPCR, migration and invasion assays were performed to reveal the clinical rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…MIR1915HG has been reported to be associated with hypoxia in gastric adenocarcinoma (39). AL157895.1 has been reported to be associated with the occurrence and development of bladder cancer (40). However, to the best of our knowledge, no previously published studies have reported on roles for the other two lncRNAs, AL512363.1 and AC010615.2.…”
Section: Discussionmentioning
confidence: 96%
“…MIR1915HG has been reported to be associated with hypoxia in gastric adenocarcinoma (39). AL157895.1 has been reported to be associated with the occurrence and development of bladder cancer (40). However, to the best of our knowledge, no previously published studies have reported on roles for the other two lncRNAs, AL512363.1 and AC010615.2.…”
Section: Discussionmentioning
confidence: 96%